IMPLEMENTASI METODE PEMBIASAAN DALAM PEMBINAAN AKHLAK SISWA KELAS VII MTS MUHAMMADIYAH POKOBULO KABUPATEN JENEPONTO - Andika Fahmil Hamdi Alim; Amin Umar; Adistian Adistian (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
The objectives of this study are: 1) To determine the morals of Class VII students at MTs Muhammadiyah Pokobulo, Jeneponto Regency 2) To determine the Implementation of the moral development method of Class VII Students at MTs Muhammadiyah Pokobulo, Jeneponto Regency. The approach used in this study uses Observation, interviews, documentation, Data analysis techniques used are Data Reduction, Data presentation (data display), Verification (drawing conclusions). The results of this study indicate that the Habituation Method at MTS Muhammadiyah Pokobulo plays an important role in shaping the moral development of students, with the principal appreciating their moral development. Although many students are polite, some still need guidance. Habitual methods through routine activities, such as flag ceremonies and dhuha prayers, are effective in shaping character. However, challenges from lack of parental support and negative social environmental influences, especially for students from remote areas, hinder moral development. Teacher commitment and cooperation with parents are the keys to success, so that students are expected to be able to internalize moral values ​​and become responsible individuals.